Heavy metal concentration in body walls of Malaysian sea cucumbers - Hawa Ismail,; Punithamalar A.,; Noor Ibrahim Mohd Sakian,; Ridwan Hashim, (penerbit ukm, 2004)
Concentrations of heavy metals were determined in the body walls of two species of sea cucumbers, Stichopus hermanni Semper and Holothuria atra Jaeger, obtained from the tidal waters off Pulau Pangkor, Perak and Pulau Kapas,Terengganu. The concentrations of Cd, Pb, Zn, and Cu were determined after acid digestion by using atomic absorption spectrometer. Mercury concentration was determined by cold vapour atomic absorption spectrometer. The levels of Cd, Pb, and Hg were significantly higher in the body walls of holothuroids from Pulau Kapas than from the same species from Pulau Pangkor (p < 0.05). The Pb content in the body walls of both the species from Pulau Kapas and Pulau Pangkor was found to be higher than the permissible level in the human body. The results obtained from our studies indicated that the uncontrolled dumping of industrial affluent from Perak, Selangor and Terengganu could possibly cause significant marine pollution problems which include heavy metal contamination, especially of Cd, Cu, Pb and Zn.